The role of social support in moderating the impact of cumulative trauma on suicidal thoughts and behaviors - Hébert, Martine; Tremblay-Perreault, Amélie; Amédée, Laetitia Mélissande (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionSuicidality in adolescence is a significant public health concern. One potential correlate of suicidality is exposure to childhood trauma. Research shows that cumulative trauma is associated with a higher risk of suicidality during adolescence, with a dose-response pattern between the number of adversities and suicidal outcomes. However, not all adolescents exposed to adversity report suicidal thoughts or behaviors, suggesting that protective factors, such as social support, may buffer this association. This cross-sectional study examined gender differences in the prevalence of suicidal thoughts and behaviors, cumulative trauma, and social support among high school students. The study also sought to determine whether cumulative trauma was related to an increased likelihood of suicidal thoughts and behaviors, and whether social support moderated the association.MethodsData were collected from a representative sample of 8,194 adolescents in Grades 9–11 in Quebec, Canada.ResultsGirls were more likely than boys to report both suicidal ideation and attempts. The number of traumas experienced was positively associated with the prevalence of suicidal ideation and attempts, with each additional trauma linked to an estimated 65%–80% increase in odds, indicating a large dose-response association. After controlling for sociodemographic characteristics, social support was associated with an attenuation of the relationship between cumulative trauma and suicidal ideation. For suicide attempts, social support showed a direct protective effect among adolescent girls, but this association was not observed among boys.DiscussionThese findings highlight the relevance of early identification and support services for youth reporting multiple adversities and lower social support.